Dielectric and Interface Properties of Aluminum-Laminated Lanthanum Oxide on Silicon for Nanoscale Device Applications - Hei Wong; Weidong Li; Jieqiong Zhang; Jun Liu (Nanomaterials)
By embedding an aluminum-laminated layer within La2O3 thin films and subjecting them to high-temperature rapid thermal annealing, a La2O3/LaAlxOy/La2O3 sandwich dielectric was formed. This structure enhances the interface properties with both the silicon substrate and the metal gate electrode, improving current conduction. Comprehensive analysis using X-ray Photoelectron Spectroscopy (XPS) revealed that this novel process not only facilitates the formation of a high-quality lanthanum aluminate layer, as indicated with Al 2p peak at 74.5 eV, but also effectively suppresses silicate layer growth, as supported by the weak Si-O signal from both the Si 2s (153.9 eV) and O 1s (533 eV) peaks at the dielectric/Si interface in the Al-laminated samples. Fourier Transform Infrared (FTIR) spectroscopy revealed a significant reduction in the OH absorption peak at 3608 cm−1 OH-related band centered at 3433 cm−1. These improvements are attributed to the aluminum-laminated layer, which blocks oxygen and hydroxyl diffusion, the LaAlxOy layer scavenging interface silicon oxide, and the consumption of oxygen during LaAlxOy formation under thermal annealing. Electrical measurements confirmed that the dielectric films exhibited significantly lower interface and oxide trap densities compared to native La2O3 samples. This approach provides a promising method for fabricating high-quality lanthanum-based gate dielectric films with controlled dielectric/substrate interactions, making it suitable for nano-CMOS and memristive device applications.